Room-temperature methanol synthesis via CO2 hydrogenation catalyzed by cooperative molybdenum centres in covalent triazine frameworks - Shengliang Zhai; Yuwei Pan; Changjing Yang; Dong Zhai; Xiaoyu Gong; Li Yang; Tie Yu; Guoqing Ren; Weiqiao Deng (Nature Communications)
Abstract Selective hydrogenation of CO2 into methanol offers an ideal route for the utilization of greenhouse gas, but it remains a great challenge to be carried out under mild conditions due to the intrinsic chemical stability of CO2. Here, we report sulfur-bridged cooperative molybdenum binuclear sites anchored on covalent triazine frameworks (denoted as Mo-S-Mo/CTF), as highly efficient active sites for CO2 hydrogenation to methanol at room temperature. Under near-ambient conditions (30 °C, 0.9 MPa), Mo-S-Mo/CTF produces methanol with 96% selectivity and a methanol synthesis rate of 21.88 μmol gMoSx −1 h−1. In-situ spectroscopic characterizations combined with theoretical calculations reveal that Mo-S-Mo/CTF favors CO2 hydrogenation into methanol via the formate pathway at room temperature instead of the CO pathway at 150 °C. The cooperation of CO2 activation on one molybdenum site and H2 splitting on the other plays a key role in high catalytic activity. Our work provides a new direction for methanol synthesis at room temperature.